Mechanical behavior of different machinable ceramic crowns using vertical and horizontal preparations: an in-vitro study - Nouh, Ingy; Rafla, Nancy; Ebeid , Kamal Khaled (Brazilian Dental Science, 2023)
Objective: the aim of this study was to compare the mechanical behavior of different ceramics when used in thinvertical preparations versus traditional horizontal preparation. Material and Methods: two stainless-steel dieswere milled to simulate a minimally invasive vertical preparation (VP) and a traditional horizontal preparation(HP) for an all-ceramic crown of a maxillary first premolar. The stainless-steel dies were duplicated using epoxyresin. Eighty monolithic crowns were milled and divided into 2 groups according to preparation design. Eachdesign group was subdivided into 4 sub-groups according to material (n=10): IPS e.max CAD (lithium disilicate),Bruxzir shaded zirconia (full contour zirconia), CeraSmart (resin nanoceramic) and CEREC Tessera (advancedlithium disilicate). The crowns were cemented on their relevant epoxy resin dies using self-adhesive resin cement.All specimens were subjected to 15,000 thermocycles and then loaded to fracture in a universal testing machine.Data were analyzed using two-way ANOVA and Tukey pair wise comparison test. Results: the fracture resistancemean values of the VP (1344 + 118 N) was significantly lower than the HP design (1646 + 191 N). Ceramiccrowns made of full contour zirconia had higher fracture resistance mean values (2842 + 380 N) than advancedlithium disilicate (1272 + 125 N) followed by lithium disilicate crowns (983 + 52 N) and resin nanoceramic(882 + 61 N). Conclusion: both vertical and horizontal preparations, regardless the different ceramic materials,showed clinically acceptable fracture resistance values.KEYWORDSDental crown; Prosthodontics; Zirconia; Lithium disilicate; Hybrid ceramics.